Various International Experiences in Waste Management - Useful Lessons for Algeria - Samiha, Bouanini; Abdessalem, Makhloufi (International Journal of Business, Economics and Management, 2015)
The environmental concern is very important because the interest of a clean environment is among the most important pillars of sustainable development. Therefore, the amount of waste we produce is the result of our unsustainable lifestyle. Most of the waste produced by human can be treated by incineration, composting or landfill. However, all these methods cause air, water and soil pollution, which is harmful to human health, plants, and animals. Therefore, developed countries promote the 3R principle (waste reduction, reuse, and recycling) which have less negative effects on the environment. However, being responsible towards waste minimization is directly linked to how a society is educated to see it. As well, being responsible is something that can be taught and learned and this can be achieved if countries are learning from the others who are achieving better in waste minimization. For that, this study had a look in several experiences in different countries such as: Austria, Germany, Belgium, Netherlands, Switzerland, USA, Japan and China to profit from various international experiences in municipal solid waste management (MSWM) and learn some useful lessons for Algeria. This research used a descriptive study to show the situation of MSWM in Algeria and in other different countries and then it discussed some initiatives made by different governments to conclude some recommendations for Algeria.